Advancements in radiochemistry and nuclear methods of analysis for safer and sustainable applications - Sosuke Han Sanada; Richard Nichida Shrestha (Institute of Computer Science (IOCS), 2023)
This research investigates radiochemistry and nuclear analysis technologies to make applications safer and more sustainable. A mathematical optimization approach optimizes radiopharmaceutical synthesis parameters for positron emission tomography (PET) imaging to maximize yield and minimize radioactive waste. Optimizing critical parameters improves the efficiency, safety, and sustainability of radiochemistry and nuclear technologies in medical imaging, nuclear energy, and environmental monitoring. The numerical example shows that optimization achieves the study goal. Optimization strategies improve medical imaging by increasing radiopharmaceutical yield and decreasing radioactive waste volume. Real-world implementation requires cost-effectiveness, safety restrictions, and numerous synthesis factors. Researchers, policymakers, and industry professionals must collaborate to enhance human and environmental welfare, according to the report. In conclusion, this research advances radiochemistry and nuclear procedures for safer and more sustainable applications, mitigating hazards and environmental effect and ensuring a safer and more sustainable future for nuclear technology.